Pengembangan Media Pembelajaran Menggunakan Instagram pada Materi Kesetimbangan Kimia Sebagai Sumber Belajar Mandiri Siswa Kelasa XI SMA - Aftika Khoirunnisa; Suryelita Suryelita (Edukimia, 2023)
Chemical equilibrium is a lesson material for 2nd grade of senior high school in chemistry subject. The material is difficult for some students to understand because the characteristics of the material are abstract and count a lot. Independent learning is required to better understand this topic. Social media can be used as an innovative source of independent learning, one of which is instagram. The utilization of this platform can attract interest in learning because most students are instagram users. But there are no accounts that have been found that use it to share chemical equilibrium learning media. The research was carried out to develop chemical equilibrium learning media using instagram and uncover its validity and practicality. The type of research is educational design research with the plomp model which consists of three stages, namely: preliminary research, prototyping stage, and assessment phase. The research is limited to prototype stage iii. The research subjects were unp chemistry lecturers, chemistry teachers, and students of sman 3 padang. Validation data processed using aiken’s v formula shows that the media is valid with a value of v = 0.9. Practicality tests on teachers and students in small groups stated that the resulting media was very practical.